Electrospinning-derived ZnCo2O4@carbon nanofiber composite for high-performance lithium ion storage. Issue 10 (15th May 2023) - Tang, Hong; Jiang, Mengjin; Bai, Wenhao; Cui, Ce; Xiao, Hongyan; Ren, Erhui; Zhou, Mi; Zhang, Jinwei; Cheng, Cheng; Guo, Ronghui
Abstract: The degradation of the cobalt-zinc oxide structure and its poor conductivity during the charge and discharge limit their further applications for lithium ion storage. Herein, ZnCo2 O4 @carbon nanofiber composite with nano-fibrous structure is obtained by electrospinning, annealing in argon and low-temperature oxidation to effectively overcome the above issue. The active sites of ZnCo2 O4 are evenly dispersed inside the carbon nanofibers, which can effectively avoid its aggregation and improve electrical conductivity. Additionally, the stable nanofibrous structure can maintain structural stability. The composite exhibits superior lithium ion storage capacity when being served as anode electrode. The ZnCo2 O4 @carbon nanofiber electrode possesses a high capacity of 1071 mA h g −1 at 0.1 A g −1 . Besides, the electrode shows an outstanding rate capability of 505 mA h g −1 at 3 A g −1 and maintain 714 mA h g −1 after 250 cycles when current density is adjusted to 0.2 A g −1 again. Additionally, the electrode has an outstanding long-cycle performance, which remains a capacity of 447.165 mA h g −1 at 0.5 A g −1 after 500 cycles and 421.477 mA h g −1 at 1 A g −1 after 518 cycles. This result demonstrates that ZnCo2 O4 @carbon nanofiber composite has potential application prospects in the fields of advanced energy storage.